ENGLISH LANGUAGE EDUCATION STUDY PROGRAM STUDENTS’ PERCEPTIONS OF USING THE ENGLISH QUIZ FILTER FEATURE ON INSTAGRAM FOR ENGLISH LANGUAGE LEARNING - Br Gultom, Jojor (Universitas PGRI Yogyakarta, 2024)
This study explored English education students' perceptions of Instagram's English quiz filter feature and its impact on their learning motivation. Using a qualitative case study approach, data were collected through observation, interviews, and documentation to address the need for engaging English learning media. The findings revealed that students view the quiz filter as engaging, enjoyable, and beneficial for improving vocabulary, grammar, and formal exam preparation like TOEFL, offering practice questions and immediate feedback. The tool's alignment with students' technological habits makes it a flexible and motivating learning medium, fostering a supportive environment where mistakes are seen as learning opportunities. Intrinsic motivation, driven by curiosity and a desire to improve English skills, enhances students' consistent use of the quiz filter. However, while the feature offers significant benefits, the study also highlights social media's potential to distract, emphasizing the need for careful management to maintain learning effectiveness